Age based lower body joint analysis of male endurance running performance - Diss, C.; Gittoes, M.; Tong, R.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to examine the age based changes in joint angles and moments throughout the stance phase of running. A biomechanical analysis was conducted on the running gait of endurance athlete from three different age groups. Reduction in ankle and knee flexion and moments was an age response to running gait. To reduce the rate of decline in running performance seen with age the training strategies employed should be ankle and knee joint focussed.